2014
DOI: 10.1021/jp505323j
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Solid Reaction of Carbon Dioxide with Alanates

Abstract: An empirical study of the gas–solid reaction of carbon dioxide (CO2) with alanates is presented. This investigation was triggered by reports of hazards related to the reaction of lithium aluminum hydride with carbon dioxide, together with the recent emergence of alanates as potential hydrogen storage materials. Furthermore, the reduction of CO2 by hydrides is an alternative to the conventional CO2 reduction employing hydrogen gas in combination with a catalyst. Experimentally this work was carried out by study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Methane and ethylene formation for reaction of CO 2 with alanates has been already reported: 16,17 nevertheless, this reaction has to be carried out at temperature higher than 120°C in order to observe sufficiently fast kinetics. 17 CO 2 reduction by BH 3 NH 3 , LiBH 4 and NaBH 4 was studied previously both theoretically 18 and experimentally, [19][20][21][22][23][24][25][26][27] as a method to enhance the thermolytic dehydrogenation of borohydrate compounds 19,20,27 or as a cheap method to obtain boron-doped carbons 21,22 or graphene oxide. 23 It was also reported that sodium and lithium borohydrides react with CO 2 to give valuable chemical products as formic acid, 26 acyloxyborohydrides 25 and formatomethoxyborate or triformatoborohydride, depending on reaction conditions (temperature and solvents).…”
Section: Fast Carbon Dioxide Recycling By Reaction With -Mg(bhmentioning
confidence: 99%
“…Methane and ethylene formation for reaction of CO 2 with alanates has been already reported: 16,17 nevertheless, this reaction has to be carried out at temperature higher than 120°C in order to observe sufficiently fast kinetics. 17 CO 2 reduction by BH 3 NH 3 , LiBH 4 and NaBH 4 was studied previously both theoretically 18 and experimentally, [19][20][21][22][23][24][25][26][27] as a method to enhance the thermolytic dehydrogenation of borohydrate compounds 19,20,27 or as a cheap method to obtain boron-doped carbons 21,22 or graphene oxide. 23 It was also reported that sodium and lithium borohydrides react with CO 2 to give valuable chemical products as formic acid, 26 acyloxyborohydrides 25 and formatomethoxyborate or triformatoborohydride, depending on reaction conditions (temperature and solvents).…”
Section: Fast Carbon Dioxide Recycling By Reaction With -Mg(bhmentioning
confidence: 99%
“…In this respect, hydrides have been employed as (i) catalysts 35 in the CO 2 hydrogenation or as pure 35,262 or as supported species. 14, 71 Moreover, their use as (ii) as co-reactants 21, [263][264][265] has been also reported. 25 …”
Section: Hydridesmentioning
confidence: 99%
“…Due to its very purpose as a moderate temperature hydrogen storage material, γ-Mg(BH 4 ) 2 cannot be heat-treated and degassed at elevated temperatures in an analogous way to other microporous materials such as activated carbons or aluminosilicates. In addition, common ScD techniques such as with CO 2 are also inapplicable since Mg(BH 4 ) 2 (as other borohydrides 25 and alanates 26 ) is well known as a powerful reducing agent that reacts with CO 2 under even mild conditions. This was reported to occur after exposure at 313 K and 9 MPa in our recent work 34 We subsequently reported 34 that the supercritical N 2 drying (NScD) methodology described herein was successful for the purification of γ-Mg(BH 4 ) 2 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…However, certain classes of materials such as so-called complex hydrides (e.g., alanates and borohydrides) present unique challenges in handling due to their strong reactivity in the presence of water or CO 2 in addition to their (perhaps intentionally tailored) instability under heating. [24][25][26] Moreover, there is great international interest in such materials as high-density hydrogen storage compounds, [27][28][29][30] and therefore also in nanostructured and/or porous varieties [31][32][33] . For the effective purification of such reactive, unstable, and nanostructured materials, ScD methods are a promising strategy.…”
Section: Introductionmentioning
confidence: 99%